A REVIEW ON HYPERHOMOCYSTEINEMIA AND ITS RISK FACTORS - SANA QURESHI, SHAIBA; KUMAR GUPTA, JEETENDRA; UPMANYU, NEERAJ (Innovare Journal of Medical Sciences, 2016)
ABSTRACT Hyperhomocysteinemia (Hhcy) is a pathological condition characterized by abnormally large levels of homocysteine in blood. Homocysteine (Hcy) is a highly reactive sulphur-containing amino acid derived from methionine, an essential amino acid. Excess homocysteine produced in the body is excreted out of the tightly regulated cell environment into the blood. It is the role of the liver and kidney to remove excess Hcy from the blood. Hyperhomocysteinemia increases the generation of ROS by activating NADPH oxidase, downregulates the endothelial nitric oxide synthase (eNOS) and thus reduces the bioavailability of nitric oxide (NO). Moreover, it increases the production of proinflammatory cytokines like tumor necrosis factor-Î± (TNF-Î±) by activating nuclear factor-kappa B (NF-ÎºB). Hyperhomocysteinemia is caused by the excess deficiencies of the vitamins like pyridoxine (B6), folic acid (B9), or B12 and is considered as an independent risk factor for various cardiovascular diseases like endothelial dysfunction, vascular inflammation, atherosclerosis, hypertension, cardiac hypertrophy and heart failure.Â 